Nelson Mandela - Nagadya Isdahl, Nansubuga (First names., 2021)
Illustrated biography of the first black South African president, Nelson Mandela, describing his childhood, his education, his professional career and political activism, his repeated imprisonment for fighting against apartheid, and how he negotiated an end to the system and was elected as president of the country.